The Role of Mobile Payment Apps in Inclusive Financial Growth - Neelam K.; Sonali Bhattacharya (Australasian Accounting, Business and Finance Journal, 2023)
In the age of technology, the usage of mobile payment apps is playing a significant role in financially strengthening urban areas. This research aiming to identify the enablers affecting the use of mobile technology by the urban poor households in Pune, Maharashtra, India and to identify the user behaviour in technology adaptation. The published literature was thoroughly reviewed with respect to mobile payment, financial technology, and financial inclusion. The data has been collected through a field survey. Simultaneously, a structural equation model is developed using Amos software and Spss is used to perform factor analysis. The theoretical framework is based on the Unified theory of acceptance and the use of technology (UTAUT-2) Model. The enablers are Performance Expectancy (PE), Economic Benefit (EB), Convenience, Technical conditions (TC), Hedonic motivation (HM), and Behavioural intention (BI), Social influence (SI) are impacting the use of mobile apps related to finance under the mediating effect of behavioral intention, thereby supporting financial inclusion. Gender, education, occupation, and income are the control variables. Men are more frequent users of mobile payment apps. This study is unique in the context of urban poor households regarding the use of m-payment app and to understand their behavior and actual usage pattern. The current study also has some implications for the banking and mobile technology industry. They may start new strategies for mobile industries and certain factors such as security, convenience, and technical conditions can influence customer intention of using m-payment apps; hence, it needs proper consideration. Simultaneously, banks and technology industries must verify their privacy norms and make it easy for customers to use technology.
Keywords: Mobile Payment App; Urban Poor Households; Structural Equation Modeling; Unified Theory of Acceptance; Use of Technology (UTAUT-2)